2021
DOI: 10.5194/nhess-21-2181-2021
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of centennial (1918–2019) drought features in the Campania region by historical in situ measurements (southern Italy)

Abstract: Abstract. Drought is a sustained period of below-normal water availability. It is a recurring and worldwide phenomenon, but the Mediterranean Basin is seen as a very vulnerable environment in this perspective, and understanding historical drought conditions in this area is necessary to plan mitigation strategies to further face future climate change impacts. The current research was aimed at the description of drought conditions and evolution for the Campania region (southern Italy), assessed by the analysis o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Overall, the longest duration of the ponding or dry-bed periods was observed in the year 2016/2017 for all the reaches studied. This longer duration is also reflected by the drought analysis conducted in Campania by Longobardi et al 22 , which showed that a severe drought period occurred in 2017. The year with the shortest NF duration is the year 2017/2018 for S1, M1, M2, M3, while for L1 reach the years 2017/2018 and 2018/2019 have a similar duration of NF period, with the latter slightly shorter.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Overall, the longest duration of the ponding or dry-bed periods was observed in the year 2016/2017 for all the reaches studied. This longer duration is also reflected by the drought analysis conducted in Campania by Longobardi et al 22 , which showed that a severe drought period occurred in 2017. The year with the shortest NF duration is the year 2017/2018 for S1, M1, M2, M3, while for L1 reach the years 2017/2018 and 2018/2019 have a similar duration of NF period, with the latter slightly shorter.…”
Section: Resultsmentioning
confidence: 78%
“…The climate is characterized by a wet season from September to May, the rainiest month is November with an average of around 90 mm, the driest month is July with an average of around 10 mm. The total annual average is around 1553 mm 22 . While, considering only the period of observation (2015–2021) it was on average 1300 mm.…”
Section: Case Studymentioning
confidence: 99%
“…However, the SRI series are autocorrelated, which influences the significance of the test results. The modified Mann-Kendall (MMK) trend test method can eliminate the autocorrelation components in the sequence and improves the testing ability of the M-K method (Hamed and Rao, 1998;Longobardi et al, 2021). Therefore, this paper adopted the MMK method to investigate the trend characteristics of hydrological drought in the HRB during 1967-2019 with the significance level of 0.05 and the corresponding |U | = 1.96.…”
Section: The Modified Mann-kendall Trend Test Methodsmentioning
confidence: 99%
“…Therefore, this paper adopted the MMK method to investigate the trend characteristics of hydrological drought in the HRB during 1967-2019 with the significance level of 0.05 and the corresponding |U | = 1.96. The calculation procedure of the MMK method was described in Longobardi et al (2021).…”
Section: The Modified Mann-kendall Trend Test Methodsmentioning
confidence: 99%
“…In the outlined context of scarcity of empirical regionalscale studies based on historical observations, the current work aims to illustrate the results in terms of inter-annual precipitation variability for a specific area, located in the Mediterranean basin. The study area is a 25,000 km 2 region located in Southern Italy and was already analyzed in the past for a climatological characterization (Longobardi and Villani 2010;Califano et al 2015;Longobardi and Mautone 2015;Longobardi et al 2016;Fattoruso et al 2017;Longobardi et al 2021). The annual precipitation in the region appeared to show a general negative trend, which was however statistically significant for only a limited number of rain gauge stations.…”
Section: Introductionmentioning
confidence: 99%